Analysis of mode of surge arrester in the presence of nonsinusoidal voltage - Шевченко, Сергій Юрійович (Technology audit and production reserves, 2015)
In the article it is considered the work of nonlinear surge arrester in quasi-stationary modes and found that similar work almost impossible. Many power engineering specialists believe that NSA works so as the valve gap. This claim is false because NSA is connected directly to the network through a gap the spark gap. Therefore NSA is constantly under the influence of the working voltage, which causes additional requirements for its parameters when a quasi-stationary over the network. The calculations of the energy dissipation of NSA under the action as part of which there are higher harmonics allow to conclude that in accordance voltage requirements of GOST on energy quality. NSA is working properly supporting thermal balance. However, NSA violation of thermal balance can occur when working in networks with a high content of harmonic oscillations, leading to its failure. Calculations are made on the basis of current-voltage characteristics of NSA, which allows determining the value of currents in the presence of voltage in the network containing harmonic oscillations.